Roux-en-Y gastric bypass versus sleeve gastrectomy: a meta-analysis - Nietz, Sarah Lena (My University, 2014)
Morbid obesity is a growing pandemic and is a direct cause of diseases such as type 2 diabetes. Bariatric surgery is an effective long-term treatment modality. There are several procedures that have been described, however, sleeve gastrectomy (SG) has gained popularity despite a paucity of evidence for its use. In contrast, the Roux-en-Y gastric bypass (RYGB) has been validated and is considered the gold standard in bariatric surgery. Currently there is no evidence proving superiority of RYGB over SG. Objectives To determine whether SG is as effective as RYGB. Methods Randomized controlled trials (RCTs) comparing adults undergoing laparoscopic RYGB or SG for treatment of morbid obesity were compared in a fixed-effect model meta-analysis. Outcomes included measures of weight loss, improvement of comorbidities, procedurerelated morbidity and mortality, and changes in gut hormone levels. Heterogeneity was assessed using the I2 test, and all studies were assessed for bias. Results Eight RCTs were included in this review. No mortalities were reported. SG had lower rates of morbidity, re-operation and re-hospitalization, but this was not statistically significant. There was no significant difference between SG and RYGB for parameters of weight loss and diabetes resolution after 12 months follow-up. RYGB significantly improved dyslipidaemia with statistical differences in triglyceride and LDL reduction (MD=-0.17, 14 p=0.05 and MD=-0.43, p=0.002 respectively). SG lowered fasting ghrelin levels (MD=342.96, p=<0.00001), RYGB lowered leptin levels (MD= -6.96, p=0.02), and there was no difference in PYY levels. Conclusions SG and RYGB were equivalent in procedural morbidity and mortality, weight loss and parameters of diabetes resolution at 12 month follow-up. RYGB had a superior resolution of dyslipidaemia.